Isotretinoin self-nano-emulsifying drug delivery system: Preparation, optimization and antibacterial evaluation - Rihaf Alfaraj; Sandra Hababah; Esra K. Eltayb; Fulwah Y. Alqahtani; Fadilah S. Aleanizy (Elsevier, 2024)
Purpose: Isotretinoin (ITN) is a poorly water-soluble drug. The objective of this study was to design a successful liquid self-nanoemulsifying drug delivery system (L-SNEDDS) for ITN to improve its solubility, dissolution rate, and antibacterial activity. Methods: According to solubility and emulsification studies, castor oil, Cremophor EL, and Transcutol HP were selected as system excipients. A pseudo ternary phase diagram was constructed to reveal the self-emulsification area. The developed SNEDDS were visually assessed, and the droplet size was measured. In vitro release studies and stability studies were conducted. The antimicrobial effectiveness against multiple bacterial strains, including Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA), and different accessory gene regulator (Agr) variants were investigated for the optimum ITN-loaded SNEDDS formulation. Results: Characterization studies showed emulsion homogeneity and stability (%T 95.40-99.20, A graded) with low droplet sizes (31.87 ± 1.23 nm-115.47 ± 0.36 nm). It was found that the developed ITN-SNEDDS provided significantly a higher release rate (>96 % in 1 h) as compared to the raw drug (<10 % in 1 h). The in vitro antimicrobial activities of pure ITN and ITN-loaded SNEDDS demonstrated a remarkable inhibitory effect on bacterial growth with statistically significant findings (p < 0.0001) for all tested strains when treated with ITN-SNEDDS as compared to the raw drug. Conclusion: These outcomes suggested that SNEDDS could be a potential approach for improving solubility, dissolution rates, and antibacterial activity of ITN.